New schiff base ligand type [LH2] donor derevative from 4-Aminophenol with Manganese (II), Cobalt(II), Nickal(II), and Copper(II) - Shaee Asaad Shahbahram; Iman Ibrahim Abdulkareem (Zanco Journal of Pure and Applied Sciences, 2023)
The condensation reaction between dimethylglyoxime, acetic acid, and 4-aminophenol was significantly influenced by the [LH2] type donor derivative ligand. The reaction was conducted in methanol for 24 hours while being stirred and refluxed. The syntheses forming a new (2E,3E)-butane-2,3-dione O2-((E)-1-((4-hydroxyphenyl)imino)ethyl) O3-((Z)-1-((4-hydroxyphenyl)imino)ethyl) dioxime) dioxime ligand type [LH2]. Spectroscopic techniques (FT-IR and UV-Vis), elemental analysis (CHN), magnetic susceptibility testing, thin-layer chromatography (TLC), X-RD powder diffraction, 1H-NMR molar conductance, and other methods have been used to characterize the ligand and its complexes with the general formula [M(LH2)] where [M= Mn(II), Co(II), Ni(II), and Cu(II), and [LH2] = donor atoms ligand with N4 and O]. Our study reveals the formation of a new ligand and new complexes with trigonal bipyramid geometrical shape around the Manganese(II), Cobalt(II), Nickel(II), and Copper(II) metal ions. Biological function using the agar disc diffusion method for the ligand and its complexes showed considerable activity against one kind of bacteria (Staphylococcus aureus) after being exposed to two types of bacteria (Staphylococcus aureus and Escherichia coli).